Failure of oxytocin and vasopressin to combine with an anti-insulin antibody (Revista Española de Fisiología, 1969)
Synthetic oxytocin and vasopressin do not exert an insulinlike action in combining with an ox anti-insulin serum. Since the only characteristic of both insulin and these peptides is the presence of a disulfide bridge, it became pertinent to show that these particular portions of the molecule per se, do not play a role in the antigen-antibody reaction.